SUICIDE RISK IN NURSING AND ITS RELATIONSHIP WITH SAFE CARE ATTITUDES - Bertussi, Vanessa Cristina; Ferreira, Lúcia Aparecida; Pereira, Lorrayne Sousa; Santana, Lucas Carvalho; Junqueira, Marcelle Aparecida de Barros (Cogitare Enfermagem, 2024)
Objective: to analyze the association between the variables of risk factors for suicide and attitudes related to patient safety among Primary Health Care Nursing professionals, and attitudes related to patient safety among Nursing professionals. Method: a cross-sectional study with a quantitative approach, with 251 nursing professionals working in Uberlândia-Brazil, carried out between July and September 2020, using the instruments: Mini International Neuropsychiatric Interview Plus and Safety Attitudes Questionnaire-Short Form. Analysis using inferential statistical methods and multiple regression. Results: negative attitudes increased by 2% among participants with health conditions or a history of suicide; around 3% among those with chronic pain or illness who were at risk of thinking of a way to commit suicide; around 7% for participants with suicidal behaviors. Conclusion: mental health, family history, and working conditions are interlinked with work attitudes.